Antibactery Activity of Etyl Asetate Fraction of Etanol Extract of Pala Leaf (Myristica Fragrans) and Lidah Buaya Leaf (Aloe Vera) Against Streptococcus Mutans - Awanis, Safirah; Mambang, D Elysa Putri; Yuniarti, Rafita; Nasution, Muhammad Amin (Pustaka Media Publishing, 2025)
Caries is a progressive chronic hard tissue disease of the teeth caused by the action of microorganisms. The bacteria that causes this disease is Streptococcus mutans. Nutmeg leaves (Myristica fragrans) and aloe vera leaves (Aloe vera) can potentially overcome diseases and health problems. This study was to determine the antibacterial activity of n-hexane fraction, ethyl acetate, ethanol extract of nutmeg leaf and aloe vera leaf in Streptococcus mutans and to determine the effect of n-hexane fraction, ethyl acetate, ethanol extract of the antibacterial of nutmeg leaf and aloe vera leaf. The method uses was an experimental method with phytochemical screening, then manufacture of ethanol extracts of nutmeg leaves and aloe vera leaves, then fractionated with ethyl acetate solvent, then testes for antibacterial activity against Streptococcus mutans by the agar diffusion method. The results of the antibacterial activity test of the ethyl acetate fraction of nutmeg leaves showed the diamete of the inhibition zones at concentrations of 50%, 40%, 30%, 20%, and 10% were obtaines with inhibition zones of 16.2 mm, 15.46 mm, 15.2 mm, 12.26 mm and 11.76 mm. The test results on aloe vera leaf ethanol extract at concentrations of 50%, 40%, 30%, 20%, and 10 % were obtained with inhibition zones of 16.53 mm, 15.13 mm, 14.3 mm, 11,5 mm, and 11.3 mm. From the results of the study, it can be concluded that simplisia, ethanol extract, ethyl acetate fraction, n-hexane nutmeg leaf and aloe vera leaf contain secondary metabolites that act as antibacterial. The antibacterial activty of ethyl acetate fraction of nutmeg leaves was highest at a concentratioan of 50% with an inhibition zone of 16.2 mm and the antibacterial activity of aloe vera leaf ethanol extract was highest at a concentration of 50% with an inhibition zone of 16.53 mm in Streptococcus mutans which can be categorized as having strong inhibitory power.